(untitled) - Harry G Summers (New York, 1985)
The book presents an exceptionally wide range of objective information on the war that divided the American people and changed the nature of global politics in the second half of the 20th century. The almanach consists of three sections: 1*) Part I provides an introductory history of VietNma from ancient time until 1959 and describes the physical setting of the country. It also analyzes the significance of VietNma's historical and physical realities in shaping American policy in th area. 2*) Part II is a detailed chronology of military and political events - both in VietNam and in America - from 1959 to the fall of Saigon in 1975. 3*) Part III, the heart of the book, contains some 500 articles, arranged alphabetically, on the people, battles, weapons, controversial issues and key concepts of the conflict. Many of these articles include cross-references and suggestions for further reading for the persons who seeks more in-depth information on a given topic. Other features that complement the lucidly written text include a selective bibliography, 21 maps and more than 120 photographs
Keywords: vietnamese conflict, 1961-1975